Association of stress hyperglycemia ratio with mortality in sepsis-associated acute kidney injury: a retrospective analysis of the MIMIC-IV database - Jing Zhang; Jiali Xia; Zheng Niu; Hongyu Zhu; Xudong Wang (Scientific Reports)
Abstract In recent years, the relationship between stress hyperglycemia ratio (SHR) and clinical outcomes in critically ill patients has garnered increasing attention. However, its role in predicting the prognosis of patients with sepsis-associated acute kidney injury (SA-AKI) remains unclear. This study aimed to clarify the relationship between SHR and all-cause mortality in patients with SA-AKI. We conducted a retrospective cohort study based on patient data from the Medical Information Mart for Intensive Care IV (MIMIC IV) database. Critically ill patients diagnosed with SA-AKI were stratified according to the quartiles of SHR. The primary outcome was all-cause mortality during hospitalization. Kaplan-Meier curve analysis was used to compare survival differences among the groups. A Cox proportional hazards model adjusted for confounding factors, was employed to investigate the relationship between SHR and mortality. A total of 1822 adult patients with sepsis-associated renal injury were included in the study. The average age was 68 years, 1059 (59.58%) were male. The patient’s increased 30-day risk of death is associated with a higher SHR index, as indicated by the Kaplan-Meier curves (log-rank P < 0.001). Furthermore, Cox proportional-hazards regression analysis revealed that the risk of mortality was significantly higher in the highest quartile of the SHR index. Restricted cubic splines (RCS) analysis demonstrated U-shaped relationships between the SHR index and 30-day mortality, with inflection points at 0.67 for 30-day mortality. Compared to patients with SHR levels below these inflection points, those with higher levels had a 38.2% increased risk for 30-day all-cause mortality (hazard ratio [HR] 1.382; 95% confidence interval [CI] 1.198–1.593). In patients with sepsis-related acute kidney injury, the SHR index can be used as an effective indicator to assess severity and guide treatment. While elevated SHR portends an increased risk of death, inadequate acute glycemic regulation also merits attention. These findings underscore the importance of SHR-based management for the prognosis of critically ill patients with SA-AKI and highlight the need for further multicenter clinical studies to establish the optimal diagnostic threshold for SHR.